2016
DOI: 10.1007/s00167-016-4404-7
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year patient-reported outcomes following total and minimally invasive unicompartmental knee arthroplasty: a propensity score-matched cohort analysis

Abstract: Purpose For patients with medial compartment arthritis who have failed non-operative treatment, either a total knee arthroplasty (TKA) or a unicompartmental knee arthroplasty (UKA) can be undertaken. This analysis considers how the choice between UKA and TKA affects long-term patient-reported outcome measures (PROMs).MethodsThe Knee Arthroplasty Trial (KAT) and a cohort of patients who received a minimally invasive UKA provided data. Propensity score matching was used to identify comparable patients. Oxford Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 43 publications
6
42
0
Order By: Relevance
“…Lim and colleagues also found no statistically significant difference in the change of function scores over time for both UKA and TKA [33]. Consistent with that, the other authors confirmed an association between better preoperative scores and better postoperative scores [34,35]. By examining patient-reported outcome measures from the National Joint Registry of England and Wales (NJR), no difference was found in the improvement of either knee-specific or general health outcomes between UKA and TKA in a large cohort [36].…”
Section: Discussionmentioning
confidence: 60%
“…Lim and colleagues also found no statistically significant difference in the change of function scores over time for both UKA and TKA [33]. Consistent with that, the other authors confirmed an association between better preoperative scores and better postoperative scores [34,35]. By examining patient-reported outcome measures from the National Joint Registry of England and Wales (NJR), no difference was found in the improvement of either knee-specific or general health outcomes between UKA and TKA in a large cohort [36].…”
Section: Discussionmentioning
confidence: 60%
“…We suggest this may be due to UKA requiring less tissue trauma and resulting in more normal knee mechanics postoperatively than TKA. 25 Thus, less pain, inflammation, and persistent mechanical alteration in knee movements overall may make 2-year functional outcomes less dependent on early pain control. Additionally, there is less surgically altered tissue in UKA, so early pain and diminished rehab would not be expected to result in multicompartmental scarring and stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to total knee replacement, the partial procedure is less invasive and is associated with a faster recovery, reduced risk of blood transfusion, fewer medical complications and lower mortality [10,12,13]. Both procedures significantly reduce pain and improve function for the majority of patients, but comparative evidence suggests that partial replacement is associated with better functional outcome [14,15]. Yet, long-term studies and registry data show that the revision rate is higher following partial than total knee replacement [12,13,16,17].…”
Section: Introductionmentioning
confidence: 99%